Declining semen quality and steadying seminal plasma ions in heat‐stressed boar model. (29th March 2015) - Li, Yansen; Wang, Aihua; Taya, Kazuyoshi; Li, ChunMei
Abstract: Purpose: There are increasing concerns about infertility of male exposure to high environmental temperatures. Nevertheless, the relationship between heat and accessory sex gland secretion underlying the high ambient temperature‐induced poor semen quality has not yet been addressed. Methods: In the present study, five boars were used as an animal model to evaluate semen quality and the secretory function of accessory sex glands. After the boars received 3 days of heat exposure, semen collection was standardized to 18 continual times with a 3‐day interval to determine the semen variables of semen volume, semen concentration, abnormal spermatozoa, seminal plasma composition, and testosterone level in the seminal plasma and serum. Results: The total sperm count was lowest by the end of week 2. The higher abnormal spermatozoa percentage were observed by the end of week 2 and persisted until week 6 after heat exposure. Additionally, there was no significant change in semen volume, testosterone level, and concentrations of ions and total protein in the seminal plasma before and after heat exposure. Conclusions: A single 3‐day heat exposure caused poor semen quality, but did not disturb accessory sex gland secretion in boars. Declining semen quality might be mainly due to the damaged germ cells, which were sensitive to elevated temperature in hot summer months.